STRATEGY FOR CHILD FRIENDLY SCHOOL POLICY IMPLEMENTATION IN BANTUL DISTRICT - Widarningsih, Ayuk (Spektrum Analisis Kebijakan Pendidikan, 2023)
This study aims to describe the CFS policy implementation strategy in Bantul Regency and the factors that support and hinder policy implementation.This study uses a descriptive-qualitative approach. The data collection techniques used are observation, interviews and documentation studies. The research subjects were the Head of the Protection and Fulfillment of Children's Rights DP3APPKB, Representatives of the Education, Sports, and Youth Office (DIKPORA) Service CFS Team, Head of the Madrasah Section of the Office of the Ministry of Religion, Representatives of School Superintendents, and Representatives of Human Resource Training and Development Office (BKPSDM) Bantul Regency. The technique used for data analysis is an interactive model belonging to Miles, Huberman, and Saldana with the steps of data reduction, data presentation, and conclusion. Evaluate the validity of the data using source triangulation.The research results obtained are as follows: 1) Implementation of CFS Policy in Bantul Regency: a) Standard implementation of the policy are six components of CFS on all school members as the target. b) Human resources include HR at the regional level, namely employees of CFS implementing organizations, and HR at the school level, which includes all school members. Financial resources come from the APBD as well as supporting infrastructure resources. c) Characteristics of the implementing organization there is an organizational structure and a clear division of labor. d) Disposition, that is, policy implementers accept the policy with full awareness and commitment to implementing the policy. e) Communication is conducted through coordination meetings every three months or if there is an urgent need. f) Environmental conditions that influence, namely social and economic conditions. 2) The strategy used to maximize CFS policy implementation is the Aggressive Strategy. 3) Factors supporting the policy are local government support and cooperative education units. The inhibiting factors are communication and environmental conditions. Keywords: Strategy, Implementation, Child-Friendly School Policy